Growth Parameters of Transplant Aman Rice (cv. BRRI dhan 52) as Influenced by Age of Tiller Seedlings, Number of Tiller Seedlings Hill-1 and Level of USG (Journal of Environmental Science and Natural Resources, 2015)
The experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh, Bangladesh to investigate the effect of age of tiller seedlings, number of tiller seedlings hill-1 and application of urea super granules (USG) on the growth parameters of transplant aman rice cv. BRRI dhan52. The experiment comprised two ages of tiller seedlings viz. 25 and 35 days old, three levels of tiller seedling hill-1 viz.1, 3 and 5 seedlings hill-1 and three USG levels viz. 0, 1.8 and 2.7g USG. The experiment was laid out in a Randomized Complete Block Design with three replications. The highest and lowest plant height was found by transplanting 25-day and 35-day old tiller seedlings at all dates of observations. By transplanting 35-day old tiller seedlings total dry matter hill-1 was found highest at 15DAT and 45 DAT. Total dry matter hill-1 was the highest in 5 tiller seedlings hill-1 and it was in lowest in 1 tiller seedling hill-1. Plant height was the highest in 5 tiller seedlings hill-1 which was as good as that of 3 tiller seedlings hill-1 and the lowest one was found in 1 tiller seedling hill-1 at 15 DAT. The tallest plant and highest total dry matter hill-1 were observed in 1.8g USG and the lowest one was observed in control treatment. Transplant Aman rice can be grown by transplanting 25-day old tiller seedling, 5 tiller seedlings hill-1 and by applying 1.8g USG for the highest plant height, more tiller and total dry matter production hill-1.DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22104 J. Environ. Sci. & Natural Resources, 6(2): 101-108 2013